Effect of endophytic Beauveria bassiana on populations of the banana weevil, Cosmopolites sordidus, and their damage in tissuecultured banana plants - Akello, J.; Dubois, T.; Coyne, Danny L.; Kyamanywa, S. (Wiley, 2008)
The entomopathogen Beauveria bassiana (Balsamo) Vuillemin (Ascomycota: Hypocreales) survives as an endophyte in a wide range of plants, offering substantial protection against tunneling insect pests. Although current research indicates that the fungus can live as an endophyte in tissue-cultured banana plants, there is no information on the efficacy of endophytic B. bassiana against the banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae). Our study aimed at determining the effects of endophytic B. bassiana on oviposition rate and populations of the banana weevil, and their plant damage. Screenhouse studies were undertaken in which 8-week-old B. bassiana-inoculated tissue-cultured banana plants [cultivar Kibuzi, Musa spec. (Musaceae), genome group AAA-EA] were infested with female banana weevils. Five days after plant infestation with the banana weevil, there was no effect of B. bassiana on oviposition rate and egg hatchability. However, after 15 weeks, the presence of B. bassiana as an endophyte in banana tissues greatly reduced banana weevil populations and their damage to plants. Between 53.4 and 57.7% of the banana weevil adults died because of B. bassiana infection, resulting in a reduction of plant damage by 29.1–62.7% depending on plant part. Beauveria bassiana was re-isolated from different plant parts, but to a greater extent from the roots and rhizomes than from pseudostem bases. Artificial inoculation of B. bassiana in banana plants caused no negative impact on banana growth. Our study demonstrated for the first time that endophytic B. bassiana reduced populations of C. sordidus and the plant damage they cause, and can thus be an alternative method for effective delivery of this fungus to banana plants for the management of C. sordidus.